Regulation of Major Plant Nutrients and Organic Matter for Improving the Nutritive Quality of Banana Grown in Laterite Soils - Binu Thomas (Department Of Soil Science And Agricultural Chemistry,College Of Horticulture, 1999)
An investigation was taken to study the regulation of major plant nutrients and organic matter for improving the nutritive qualities of banana. The expriment was laid out at Banana Research Station, Kannara, Kerala Agricultural University during the period 1996-97. The result of this study revealed that application of fertilizer and organic matter is essential for getting better yield and quality of banana. All the food nutrients studied were increased by the application of fertilizer and hence the quality is much improved. Regarding bunch yield the fertilizer dose of 12.5 kg FYM, 200: 125:300 g N, P205 and K20 per plant obtained maximum yield. The treatments receiving medium level of FYM and nitrogen recorded higher content of carbohydrate. Protein content of banana was increased by the application nitrogen and potassium. Application of farmyard manure enhanced the fat content of banana. Sugar content of the banana fruit is increased by the application of nitrogenous and potassium fertilizers. Acidity is increased by the application of farmyard manure and nitrogen. Nitrate accumulation in banana was high in plots receiving highest dose of nitrogen. Nitrogenous fertilizers increased the carotene content of banana. Fertilizer application enhances the total mineral content of banana due to increased uptake and availability of nutrients. Fibre content was high in fertilized plots compared to absolute control. The nitrogen content of edible portions of banana was high in plots receiving higher doses of nitrogen. The treatment T6 and T\3 which received highest dose of phosphorus (200 g/plant) recorded highest content of phosphorus. Vitamin C content was enhanced by the application of nitrogenous fertilizer and farmyard manure. Correlation studies revealed that the content of l1ajor nutrients in soil at 2, 4 and 6 months after planting has got much influence on the quality parameters studied. Hence fertilizers should be applied in split doses commencing from 2